2014
DOI: 10.1016/j.procs.2014.11.074
|View full text |Cite
|
Sign up to set email alerts
|

Arm Exoskeleton for Rehabilitation Following Stroke by Learning Algorithm Prediction

Abstract: Stroke is a major cause of disability in worldwide and also one of the causes of death after coronary heart disease. Many devices had been designed for hand motor function rehabilitation that a stroke survivor can use for bilateral movement practice. This paper presents an arm motor function rehabilitation device where it is designed to predict the position angle for the robotic arm. MATLAB software is used for real-time positioning that can be developed by SIMULINK block diagram and proof by the simulator in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The concept of feature selection pertains to identifying the optimal amalgamation of predictor variables that holds the greatest influence on the predictive model. A study using a 3R horizontal robot showed that by using all kinematic variables as input predictors for the ANN model was able to produce high predictive performance [31]. In addition, a study conducted utilizing Kinect employed over twelve predictors in the ANN model, yielding substantial predictive performance in estimating the FMA clinical score of stroke subjects [32].…”
Section: Feature Selectionmentioning
confidence: 99%
“…The concept of feature selection pertains to identifying the optimal amalgamation of predictor variables that holds the greatest influence on the predictive model. A study using a 3R horizontal robot showed that by using all kinematic variables as input predictors for the ANN model was able to produce high predictive performance [31]. In addition, a study conducted utilizing Kinect employed over twelve predictors in the ANN model, yielding substantial predictive performance in estimating the FMA clinical score of stroke subjects [32].…”
Section: Feature Selectionmentioning
confidence: 99%
“…With respect to upper limb rehabilitation, there are robotic systems that are designed for various purposes and functionalities such as assisting various upper limb movements and rehabilitation of affected upper limbs due to paralysis caused by various conditions. Many robotic systems and frameworks have been developed mainly for the rehabilitation of upper limbs with disabilities caused by paralysis due to stroke and hemiplegia [93][94][95][96]. According to Maciejasz et al [97], there are robotic systems developed to assist the following types of upper limb joint movements-shoulder movements, elbow movements, forearm movements, wrist movements, and finger movements.…”
Section: Upper Limb Rehabilitationmentioning
confidence: 99%
“…Studies have been carried out, such as [3,4,5,6,7,8] who offer exoskeletons for rehabilitation assistance, but their non-mobile system, price or operational complexity prevents them from being easily used by patients without professional staff, nor can they use it without going to a specialized place. It is necessary to improve the rehabilitation assistance so that the exoskeletons used in this application area, are easy to use, inexpensive and meet design criteria that also allow easy maintenance and repair, as well as portability.…”
Section: Introductionmentioning
confidence: 99%